The Effect of Comedication With a Conventional Synthetic Disease‐Modifying Antirheumatic Drug on Drug Retention and Clinical Effectiveness of Anti–Tumor Necrosis Factor Therapy in Patients With Axial Spondyloarthritis. Issue 9 (25th August 2016) - Nissen, Michael J.; Ciurea, Adrian; Bernhard, Jürg; Tamborrini, Giorgio; Mueller, Ruediger; Weiss, Bettina; Toniolo, Martin; Exer, Pascale; Gabay, Cem; Finckh, Axel; ,
Abstract : Objective: To explore the effect of comedication with conventional synthetic disease‐modifying antirheumatic drugs (DMARDs) on drug retention and clinical effectiveness of tumor necrosis factor inhibitors (TNFi) in patients with axial spondyloarthritis (SpA). Methods: The study included all patients starting treatment with a TNFi in a large prospective cohort of axial SpA patients (Swiss Clinical Quality Management in axial SpA). Crude drug retention was analyzed using the Kaplan‐Meier method, and in adjusted analyses, Cox proportional hazards regression was used to model TNFi discontinuation. We evaluated multiple disease activity measures and validated clinical response criteria over time. Results: A total of 2, 765 TNFi treatment courses were included from 1, 914 patients with axial SpA, 20.4% in combination with a conventional synthetic DMARD. In unadjusted analyses, the monotherapy group had significantly shorter median TNFi retention time (32.7 months) compared to the cotherapy group (39.1 months) ( P = 0.04). In multivariate adjusted analyses, the monotherapy group had significantly lower TNFi retention, with a hazard ratio (HR) of 1.17 (95% confidence interval [95% CI] 1.01–1.35). This effect was even larger when only infliximab‐treated patients were considered, with an HR for monotherapy of 1.36 (95% CI 1.06–1.74). Clinical response rates were almost identical at 1 year, with a change in the Bath Ankylosing Spondylitis Disease Activity Index of −2.02 and −2.00 ( P = 0.83) and a change in the Ankylosing Spondylitis Disease Activity Score using C‐reactive protein of −1.14 and −1.12 ( P = 0.45) in the monotherapy and cotherapy groups, respectively. Conclusion: We demonstrate an association between the combination of a TNFi with conventional synthetic DMARDs and improved drug retention in patients with axial SpA, particularly in the subgroup of patients with infliximab.